Growth and Characterization Studies of 2-Bromo-4-chloroacetophenone Crystals - ANBUSRINIVASAN, P.; KAVITHA, S. (Asian Journal of Chemistry, 2010)
The crystals of 2-bromo-4-chloroacetophenone (BCAP) were grown from carbon tetrachloride as solvent using slow evaporation technique at room temperature. Transparent, good quality BCAP crystals were successfully grown. Solubility studies were made using this solvent at various temperatures. The various functional groups present in the grown crystal have been identified using FTIR spectra. The grown crystals were subjected to 1H NMR studies and thermal studies in order to confirm the structure and purity of the grown crystals, respectively. The transparency of the crystal were tested using UV-Visible spectral analysis. Solubility and metastable zone width studies of BCAP in CCl4 have been carried at various temperatures. SHG efficiency of the grown crystals was analyzed by kurtz powder technique.